PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK SUHU DAN KALOR DIKELAS X SEMESTER II SMA NEGERI 1 SILIMA PUNGGAPUNGGA - Sirait, Makmur; Siaen, Euodia (JURNAL IKATAN ALUMNI FISIKA, 2016)
The aim of this study was to determine the effect of inquiry learning model to the learning outcomes of students in the subject matter of Temperature and Heat in the tenth grade second semester of SMAN 1 Silima Punggapungga. The research was a quasi-experimental research design two group pretest-posttest design. The population in the study were all students of class X Semester II consists of 6 classes. Sampling was done by cluster random sampling is class X-3 as the experimental class that numbered 30 people and Class X-4 as a control class that numbered 30 people. The instruments used there are 2 of tests of learning outcomes in essay form with 10 questions and the number of observation sheet activity.Â  The instrument must first be validated by the validator, and hypothesis testing using t test. From the analysis of data obtained by the average value of the experimental class pretest of 21.73 with a standard deviation of 7.56 and average value control class is 21.2 with a standard deviation of 6.35. The average value of students learning activities at the first meeting amounted to 56.11%, the second meeting of 71.38% and 80.55% for the third meeting. Average values ââobtained post test experimental class at 70.86 with a standard deviation of 8.29 and grade control of 63.06 with a standard deviation of 7.71. Of normality and homogeneity test showed that the data were normally distributed and homogeneous. The results of data processing post test obtained then H accepted that there is influence of inquiry learning model to the learning outcomes of students in the subject matter of Temperature and Heat in the tenth grade second semester SMA Negeri 1 Silima Punggapungga.